Reducing birth defects : meeting the challenge in the developing world - Bale, Judith R.; Stoll, Barbara J.; Lucas, Adetokunbo O. (National Academies Press, 2003)
Each year more than 4 million children are born with birth defects. This book highlights the unprecedented opportunity to improve the lives of children and families in developing countries by preventing some birth defects and reducing the consequences of others. A number of developing countries with more comprehensive health care systems are making significant progress in the prevention and care of birth defects. In many other developing countries, however, policymakers have limited knowledge of the negative impact of birth defects and are largely unaware of the affordable and effective interventions available to reduce the impact of certain conditions. Reducing Birth Defects: Meeting the Challenge in the Developing World includes descriptions of successful programs and presents a plan of action to address critical gaps in the understanding, prevention, and treatment of birth defects in developing countries. This study also recommends capacity building, priority research, and institutional and global efforts to reduce the incidence and impact of birth defects in developing countries.